Sectoral and structural convergence in Asean economies - Chong, Choy Yoke (2016)
Income convergence is the key to allow further economic integration among Association of Southeast Asia Nation (ASEAN) member states, and to ensure greater integration with other partner countries. However, the gap between ASEAN-6 and less developed members (Cambodia, Laos, Myanmar and Viet Nam) remained an issue to be resolved in order to facilitate further integration. Limited analysis was identified on the sectoral data despite the importance of sectoral income and production structure to aggregate income convergence. Four specific objectives of study were formed: (1) to examine convergence in both the aggregate income and sectoral income, (2) to investigate possible emergence of convergence club, (3) to examine whether ASEAN member states experienced structural convergence and (4) to determine the source of income convergence within ASEAN. Stochastic convergence was examined among member states in the ASEAN from 1970 to 2012.It is found that the aggregate income of the Philippines, Cambodia, Laos and Viet Nam were catching-up with the average income of ASEAN. Meanwhile, more evidences of catching-up were detected within the manufacturing sector (Cambodia, Laos and Viet Nam) and construction sector (Indonesia, Malaysia, Singapore and Brunei). The CLV countries were performing well in the manufacturing sector leading to the catching-up in their aggregate income with regional average. The log t convergence test was employed for both the aggregate and sectoral income in detecting possible convergence club. There were no convergence in ASEAN as a whole in aggregate income but the growth rate of Singapore, Brunei, Indonesia, Viet Nam and Myanmar converged. The ASEAN members showed convergence in their growth rates in the manufacturing, construction, mining and utilities sector as well.Weak convergence was observed in service sector while non-convergence was identified in the agriculture sector. Singapore diverged with the rest in the agriculture sector. On the other hand, the inter-sectoral heterogeneity index and Krugman index was calculated for testing the structural convergence. Both the indices asserted that ASEAN member states had achieved a larger extent of structural convergence although not perfectly homogenized. The breakdown of Krugman indices revealed that mining and utilities sector to slow down the structural convergence for all and the agriculture sector among CLMV countries. Therefore, reformation in agriculture sector among CLMV countries is needed to further expand their productivity growth for industrialization. The decomposing methodology enables the aggregate convergence to be categorised into the productivity growth effect within sector and the changing sectoral composition due to structural change. The outcomes explained that sectoral productivity growth dominated over the effect of structural change in ASEAN. In contrary to the literature, mining and tilities sector was the primary contributor to the catching-up process in ASEAN. Therefore, the expansion of these extractive industries is crucial in sustaining further development. The service sector and manufacturing sector remained their importance in driving the convergence process in ASEAN.